If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 74 = 26 + 8v Solving 74 = 26 + 8v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-8v' to each side of the equation. 74 + -8v = 26 + 8v + -8v Combine like terms: 8v + -8v = 0 74 + -8v = 26 + 0 74 + -8v = 26 Add '-74' to each side of the equation. 74 + -74 + -8v = 26 + -74 Combine like terms: 74 + -74 = 0 0 + -8v = 26 + -74 -8v = 26 + -74 Combine like terms: 26 + -74 = -48 -8v = -48 Divide each side by '-8'. v = 6 Simplifying v = 6
| -6y+30=-45 | | 100*10m=15m | | 10+7q=15+6q | | 2.6-8n=5n+19 | | 9+7x=6x+20 | | 8x-44=52 | | -0.2(x-6)=6 | | 11m^5= | | 4(d+2x)-5=3(3x+7) | | 7x-15=5x+7 | | 2c-5=c+9 | | x+x+81=x+144 | | -6+3w=-21 | | -6t-12-6t=10(t+5)+4 | | 2[1-3(w+2)+2(w+3)]=5w | | x-5-(-2)+2x=7 | | Q-2.4=1.8 | | 3b=6v+3b | | 10y+18=-3(5y-7)+5y | | 4n^2-4n-6=0 | | K-56=107 | | y+5=-7x-21 | | x^2-y^2-3x+3= | | x+x+2+x+2=75 | | (x^2-2x-1)+(2a^2+2a+3)= | | 3g+2(-5+2g)=1-g | | 2(a+1)+4a=-10 | | x^2(x^2+x+1)=0 | | 8(p+1)-6p=24 | | 5(x+4)=3x+14 | | 625=(x^2)+(x^2)+6x+9 | | 9k-32=6k+8 |